Sintesis Nanoemulsi dari Ekstrak Kulit Manggis dengan Metode Energi Tinggi - Tri Rizki; Sedarnawati Yasni; Tjahja Muhandri; Sri Yuliani (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2023)
Mangosteen (Garcinia mangostana L.) has become the main agricultural products contributing to the largest annual foreign exchange from the fruit category. Mangosteen rind contains xanthone compounds as a source of antioxidants, with α-mangostin and γ-mangostin, as the main components which are used as traditional and modern ingredients to treat various diseases. However, mangosteen rind extract has low bioavailability thus resulting in low effectiveness in the application. This study aimed to find the ideal formulation for producing the extract and nanoemulsion of mangosteen peel. The research carried out in two stages: extraction of mangosteen peel and production of nanoemulsion. Ethanol 70% was the best for mangosteen rind extraction, with a percentage yield of 40.96±0.51%, antioxidant activity of 5708.33±159.57 µg AEAC/mL sample, and total xanthones of 373.84±6.49 µg/mL sample. The use of Tween 20 at nanoemulsion production gave the best test results, with particle size of 10.58±1.25 nm, polydispersity index 0.27±0.03, zeta potential -2.34±0.46 mV, and total xanthones 35,28±0,04 µg/mL sample.